2021
DOI: 10.3390/agronomy12010055
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bush yam (Dioscorea praehensilis Benth) as a Source of Agronomic and Quality Trait Genes in White Guinea yam (Dioscorea rotundata Poir) Breeding

Abstract: Yam (Dioscorea spp.) is an important food security crop in the tropics and subtropics. However, it is characterized by a narrow genetic base within cultivated and breeding lines for tuber yield, disease resistance, and postharvest traits, which hinders the yam breeding progress. Identification of new sources of desirable genes for these traits from primary and secondary gene pools is essential for this crop improvement. This study aimed at identifying potential sources of genes for yield and quality traits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Of the cultivated species, accessions of D. dumetorum, D. alata, and D. praehensilis had better tolerance than the popular preference species for consumption (D. rotundata) and, as such, can be considered in breeding programs for the improvement of D. rotundata, particularly D. praehensilis due to their similar genome information [38]. This corroborates the findings of Adewumi et al [39], who observed better tolerance of D. praehensilis genotypes over that of D. rotundata for YMV severity. Accessions of D. praehensilis and D. rotundata had the best genetic tolerance to YAD severity among the considered species while D. alata had the least tolerance.…”
Section: Performance Of Landrace Accession Against Standard Check Gen...supporting
confidence: 87%
“…Of the cultivated species, accessions of D. dumetorum, D. alata, and D. praehensilis had better tolerance than the popular preference species for consumption (D. rotundata) and, as such, can be considered in breeding programs for the improvement of D. rotundata, particularly D. praehensilis due to their similar genome information [38]. This corroborates the findings of Adewumi et al [39], who observed better tolerance of D. praehensilis genotypes over that of D. rotundata for YMV severity. Accessions of D. praehensilis and D. rotundata had the best genetic tolerance to YAD severity among the considered species while D. alata had the least tolerance.…”
Section: Performance Of Landrace Accession Against Standard Check Gen...supporting
confidence: 87%
“…Poor agronomic potential concerning yield (<10 ton/ ha) compared to other yamproducing countries (>10 ton/ha), tolerance to pathological diseases and insect pests of many landraces seasonally cultivated by local farmers (Adewumi et al, 2022;Agre, Dassou, et al, 2021;Jeancy et al, 2021) 4 Non-commitment to providing stake support for yam establishment (Adejumobi, Agre, Onautshu, Adheka, Cipriano, et al, 2022) 5…”
Section: S/ N Yam Production Constraints Sourcementioning
confidence: 99%
“…High positive correlations were observed for the tuber traits. Positive correlations for tuber traits were also observed in studies characterizing 100 D. alata accessions (Agre et al 2019), as well as D. praehensilis and D. rotundata accessions (Adewumi et al 2022). The correlations related to tuber descriptors are relevant, as tuber yield and quality traits are considered important for selection and breeding of yam varieties (Adewumi et al 2022).…”
Section: Discussionmentioning
confidence: 75%